Adolescent clients' perceptions of maternity care in KwaZulu-Natal, South Africa - Duggan, Ravani; Adejumo, O. (Elsevier, 2012)
Background: Adolescent pregnancy continues to pose a challenge in both the developed and developing countries across the globe. Adolescent maternity clients (AMCs) have special needs and it is imperative to ensure that maternity services are able to respond appropriately to their needs. Objective or question: The purpose of this study was to explore adolescent maternity clients’ perceptions of maternity care and to identify important characteristics of an adolescent-friendly maternity service. Method: A qualitative approach was used and a total of 18 adolescent maternity clients, between 15 and 19 years of age, were purposively recruited from antenatal and postnatal services. Data were collected through individual and group interviews. Findings or discussion: Findings fell into 3 categories: AMC-health care provider (HCP) interaction; health care system; and health education. Participants wanted HCPs to be caring and supportive. Additionally HCPs should use appropriate interaction and body language to make adolescent clients feel respected and comfortable within the health care setting. Participants expected clinic waiting times to be decreased and measures to make the waiting rooms comfortable be put in place. AMCs also expressed the importance of having extra support during labour and birth. Health education was perceived as essential to their preparation for childbirth and parenting, with them having a role in peer education. Conclusion: The relationship between the HCP and AMC is essential to ensuring an optimal outcome for mother and baby. Careful consideration needs to be given to how the health care facility and system are set up in order to ensure that the AMC is comfortable within this context.